A dimensão ressocializadora da leitura no contexto da remição de pena: uma análise sobre os projetos de leitura desenvolvidos nas penitenciárias do Estado do Pará - MONTEIRO, Mariana Martins (2018)
This paper discusses the importance of reading as a remission of sentence inside penitentiaries. It presents the importance of reading within the prison library as one of the main tools for the resocialization of the prisoner by reading. The objective is to raise and evaluate the projects developed that help in the resocialization of the prisoners, using the reading for remission of sentence. The methodology was based on an applied research, characterizing the approach of the problem in quantitative-qualitative way, the object as exploratory research, the method in which the approach is problematic and the method related to the procedure was historical. The bibliographic and documentary research was used on the technical procedure. The information materials used were articles, books, legislation, jurisprudence, dissertations, etc. As a result of the discussion, it was observed the importance of the reading projects within the penitentiaries of the State and the country, as well as the implantation of the libraries inside the jail, together with the interdisciplinarity of the professionals working inside the prison.